Prevalence, characteristics and mortality of cancer patients undergoing pericardiocentesis in the United States between 2004 and 2017 - Andrija Matetic; Bonnie Ky; Eric H. Yang; Phyo K. Myint; Muhammad Rashid; Shelley Zieroth; Timir K. Paul; Ayman Elbadawi; Mamas A. Mamas (Cancer Medicine, 2023)
Abstract Background Pericardiocentesis is undertaken in patients with cancer for diagnostic and therapeutic purposes. However, there are limited data on the frequency, characteristics and mortality of patients with different cancers undergoing pericardiocentesis. Methods All hospitalisations of adult cancer patients (≥18 years) in the US National Inpatient Sample between January 2004 and December 2017 were included. The cohort was stratified by discharge code of pericardiocentesis and cancer, using the International Classification of Diseases. The prevalence of pericardiocentesis, patient characteristics, cancer types and in‐hospital all‐cause mortality were analysed between cancer patients undergoing pericardiocentesis versus not. Results A total of 19,773,597 weighted cancer discharges were analysed, out of which 18,847 (0.1%) underwent pericardiocentesis. The most common cancer types amongst the patients receiving pericardiocentesis were lung (51.3%), haematological (15.9%), breast (5.4%), mediastinum/heart (3.2%), gastroesophageal (2.2%) and female genital cancer (1.8%), whilst ‘other’ cancer types were present in 20.2% patients. Patients undergoing pericardiocentesis had significantly higher mortality (15.6% vs. 4.2%, p < 0.001) compared to their counterparts. The presence of metastatic disease (aOR 2.67 95% CI 1.79–3.97), weight loss (aOR 1.48 95% CI 1.33–1.65) and coagulopathy (aOR 3.22 95% CI 1.63–6.37) were each independently associated with higher mortality in patients who underwent pericardiocentesis. Conclusion Pericardiocentesis is an infrequent procedure in cancer patients and is most commonly performed in patients with lung, haematological and breast cancer. Cancer patients undergoing pericardiocentesis have increased mortality, irrespective of the underlying cancer type.